Technoeconomic assessment of biopolymer production from crustacean waste with the uk as a case study - GÜNDÜZ, OĞUZHAN; ULAĞ, SONGÜL (My University, 2023)
© 2023 by the authors.Marine pollution has increased in recent decades, largely due to the proliferation of seafood processing plants and the improper disposal of their associated waste streams. The waste streams consist mainly of shells that are composed of chitin, which is the most abundant aminopolysaccharide biopolymer in nature. Recognizing the value of chitin, the potential for the valorization of crustacean waste for chitin production was explored. In this regard, biogenic crab waste was subjected to chemical-only, enzymatic–chemical, and microbial treatments for chitin production. The results were employed as inputs for process simulation as a precursor to undertaking performance assessments. This study subsequently showed that the net present values (NPVs) of the chemical-only, enzyme–chemical, and microbial chitin production pathways were GBP 118.63 million, GBP 115.67 million, and GBP 132.34 million, respectively, indicating that the microbial chitin production pathway constituted the most appropriate technology for future investment. Employing a cost–benefit (CB) analysis, the CB ratios for the chemical-only, enzymatic–chemical, and microbial approaches were determined to be 7.31, 0.45, and 0.23, respectively. These results reinforced the dominant status of the microbial approach for chitin production from crab waste as the preferred valorization strategy. This study was able to provide information regarding the implications of executing alternative scenarios for crustacean waste.
Keywords: Sosyal ve Beşeri Bilimler; Coğrafya; Sosyoloji; Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Çevre Mühendisliği; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Bilgisayar Bilimleri; Donanım; İnşaat Mühendisliği; Yapı; Mühendislik ve Teknoloji; Social Sciences and Humanities; Geography; Sociology; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Environmental Engineering; Information Systems, Communication and Control Engineering; Computer Sciences; Equipment; Civil Engineering; Structure; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Sosyal Bilimler (SOC); Çevre / Ekoloji; Bilgisayar Bilimi; Mühendislik; Yerbilimleri; Sosyal Bilimler Genel; ÇEVRE BİLİMLERİ; BİLGİSAYAR BİLİMİ, DONANIM VE MİMARLIK; TELEKOMÜNİKASYON; ENERJİ VE YAKITLAR; İNŞAAT VE YAPI TEKNOLOJİSİ; COĞRAFYA; ÇEVRE ÇALIŞMALARI; Agriculture & Environment Sciences (AGE); Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Social Sciences (SOC); ENVIRONMENT/ECOLOGY; COMPUTER SCIENCE; ENGINEERING; GEOSCIENCES; SOCIAL SCIENCES, GENERAL; ENVIRONMENTAL SCIENCES; COMPUTER SCIENCE, HARDWARE & ARCHITECTURE; TELECOMMUNICATIONS; ENERGY & FUELS; CONSTRUCTION & BUILDING TECHNOLOGY; GEOGRAPHY; ENVIRONMENTAL STUDIES; Bilgisayar Bilimi (çeşitli); Fizik Bilimleri; Coğrafya, Planlama ve Geliştirme; Sosyal Bilimler ve Beşeri Bilimler; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Yapı ve inşaat; Çevre Bilimi (çeşitli); Enerji Mühendisliği ve Güç Teknolojisi; Donanım ve Mimari; Bilgisayar Ağları ve İletişim; Yönetim, İzleme, Politika ve Hukuk; Computer Science (miscellaneous); Physical Sciences; Geography, Planning and Development; Social Sciences & Humanities; Renewable Energy, Sustainability and the Environment; Building and Construction; Environmental Science (miscellaneous); Energy Engineering and Power Technology; Hardware and Architecture; Computer Networks and Communications; Management, Monitoring, Policy and Law; chitin; circular economy; technoeconomic assessment; United Kingdom seafood industry; chitin; technoeconomic assessment; United Kingdom seafood industry; circular economy